Examining emerging ICT's adoption in SMEs from a dynamic process approach. Issue 1 (25th February 2014) - Chinedu Eze, Sunday; Duan, Yanqing; Chen, Hsin
Abstract : Purpose: – This paper aims to advance information and communication technologies (ICT) adoption research and practice by examining and understanding the emerging ICT adoption in small and medium enterprises (SMEs) from a dynamic process perspective using actor-network theory (ANT). Design/methodology/approach: – This study employs a qualitative approach to investigate how services SMEs are constantly engaging in ICT adoption for improving business performance. Two rounds of interviews were conducted with 26 interviewees. Data collected from the unstructured and semi-structured interviews were analysed to understand the dynamic adoption process, actors involved and their interactions. Findings: – The findings reveal the recursive and dynamic nature of the emerging ICT adoption process and the constant interactions and negotiations of various actors. Underpinned by the key concepts of ANT and validated by the empirical data, a framework is developed to depict the stages of dynamic process of emerging ICT adoption, the actors involved and the associated key activities. Research limitations/implications: – Qualitative research is interpretive in nature and the size of the sample used is limited. These limitations require caution for the generalization of the findings. The framework can be further validated across a wider population using mixed methods combining qualitative and quantitative approaches. Practical implications: – Emerging ICT adoption has moved from a simple adopters' participation process to involving various actors that constantly interact and influence the process. SMEs manager can be influenced by and influence the technology advancement. As a result, SMEs need constantly interact with various human and non-human actors to keep up with the new ICT development and benefit from the emerging opportunities. Originality/value: – The research focuses on the emerging ICT adoption in SMEs from the dynamic process perspective using ANT. It advances ICT adoption research and practice by developing a framework to depict the dynamic and interactive nature of ICT adoption process, and the actors involved and their interactions in the adoption process.